Assessment of Sexual Behavior, Unmet Reproductive Health Needs and Fertility Intention of People Living with HIV/AIDS, Jimma, South West of Ethiopia (Global Journal of Medical Research, 2013)
Providing effective reproductive health service to people living with HIV/AIDS requires understanding of their sexual behavior, fertility intention and unmet reproductive needs. Failure of having evidence based responses on gaps identified on these needs might bring an increased HIV incidence, unintended pregnancies, vertical transmission, stigma and discrimination. Facility based cross sectional study was conducted in southwest town of Jimma, Ethiopia. Quantitative data was collected 632 study participants from the ART. A structured interview administered questionnaire was used to collect the data. Verbal and written consent was obtained from each client and data was collected by nurses. Data was analysed by SPSS version16 windows software. Most of the respondents 341(54.0%) were females, with a mean age of 29.6 ± 7.98 years. Most 86.7% were sexually active, of which 499(80.0) were had a regular partner. Casual sex was reported to be 35 (6.4%). Unprotected sexual contact was found to be 16.2% among male and 4.4% among females. Disclosure of own sero-status to partner was 90.7% while knowledge of Sexual Partner HIV status was 91.4%. Only 385 (70.3%) used condom always the remaining 163 (29.7%) used condom sometimes.